Issue frequency and convertible bonds in Malaysia - Sri Noor 'Aishah, Mohd Salleh (2017)
This study aims to investigate the impact of convertible bonds offerings announcements on the firms‟ stock returns in Malaysia. The study examines a total of 90 issuances of convertible bonds from year 2000 until 2015. Event study is performed to measure the impact of announcements on the firms‟ returns. Generally, the findings report that there is a significant impact when firms announce the issuance of convertible bonds. In addition, it is found that multiple issuers face more significant negative abnormal stock returns compared to single issuers. It is possibly due to the types of convertibles issued by multiple issuers such as Irredeemable Convertible Unsecured Loan Stocks (ICULS) and Redeemable Convertible Loan Stocks (RCLS). The issuance of ICULS and RCLS are found to lead to negative abnormal returns while the issuance of Convertible Unsecured Loan Stocks (CULS) leads to positive abnormal returns. When the subsample of multiple issuers is further categorized and analysed according to each sequence of issuance, the result is found to be driven by first issuance while insignificant on the subsequent issuance. The pattern is attributable to the decrease of information asymmetry between each issuance. Additionally, this study examines the impact of other factors that may contribute to the firms‟ abnormal stock returns. There are two variables found to be significantly related to the abnormal return at these event window; (-1, 0) and (-10, 60). In the event window for a shorter period, the variables are issuance size and the firms‟ size. In the longer period, the significant variables are frequency and purpose of issuance. The findings from this study contributes to the literature as the evidence on the impact of the convertible bonds issuance frequency on firms‟ stock returns in a developing market is relatively less explored. The study also offers some recommendations for future researches.